Manipulative Movement Based on Information Technology Games for School Children Aged 10-12 Years - Hardika, Nevi; Asmawi, Moch.; Tangkudung, James; Dlis, Firmansyah; Hanif, Achmad Sofyan; Winarno, M.E.; Sukur, Abdul; Widiastuti, (International Journal of Psychosocial Rehabilitation, 2020)
Manipulative movements are a series of movements that involve members of the body as a form of action to control an object using energy so that they can engage in movement activities that have a target or goal. Games are movement activities that are loved by all groups of children. which involves feeling happy, carefree or happy. Information technology is a set of hardware and software that is important in improving the quality of information quickly and with quality. Therefore it is very good and effective if the development of information technology is implemented in the world of sports, one of which is in the form of games for schoolchildren aged 10-12 years so as to facilitate the stages of the learning process in carrying out a variety of good and correct basic motion activities. The purpose of this study is to determine the basic manipulative movement skills in games and the effectiveness of available information technology. This research method uses Borg & Gall research and development with qualitative and quantitative approaches for OneGroup Pretest-Posttest Design. So the results obtained through Information Technology in the game will be able to improve basic movement skills that are good and right. It was concluded that the model developed in an information technology-based game can enhance symmetrical manipulation of multilateral basic movements, good and right, especially at the age of 10-12 years and the formation of emotional maturity, a sense of togetherness and effective communication among others and efficiently.